(untitled) (Analele Universității București. Limba și literatură română, 2025)
This paper proposes a comparative study of the libretto of Le Duc d’Albe, planned by Donizetti in 1839-1840 but never created during his lifetime, and that of Verdi’s Les Vêpres siciliennes, created in Paris in 1855 (by Eugène Scribe and Charles Duveyrier). This article examines: the correspondence – or not – between the characters and their evolution; the progression of the structure and the plot from one work to the other – where Verdi intervenes, while also keeping in mind the intermediate plot envisaged by Scribe and focusing on three aspects that stand out more (the scene of the recognition of the son, the question of marriage, and the insurrectional denouement); the scores and the place of versification in their arrangement.